A New Caledonian crow (Corvus moneduloides) creatively re-designs tools by bending or unbending aluminium strips. - Weir, A; Kacelnik, A (2006)
Previous observations of a New Caledonian crow (Corvus moneduloides) spontaneously bending wire and using it as a hook [Weir et al. (2002) Science 297:981] have prompted questions about the extent to which these animals 'understand' the physical causality involved in how hooks work and how to make them. To approach this issue we examine how the same subject ("Betty") performed in three experiments with novel material, which needed to be either bent or unbent in order to function to retrieve food. These tasks exclude the possibility of success by repetition of patterns of movement similar to those employed before. Betty quickly developed novel techniques to bend the material, and appropriately modified it on four of five trials when unbending was required. She did not mechanically apply a previously learned set of movements to the new situations, and instead sought new solutions to each problem. However, the details of her behaviour preclude concluding definitely that she understood and planned her actions: in some cases she probed with the unmodified tools before modifying them, or attempted to use the unmodified (unsuitable) end of the tool after modification. Gauging New Caledonian crows' level of understanding is not yet possible, but the observed behaviour is consistent with a partial understanding of physical tasks at a level that exceeds that previously attained by any other non-human subject, including apes.